Development of Excel-Based Building Defect Management System Using Business Process Reengineering in Education Building - Abdi Telaga; Thyana Avianto; Andreadie Wicaksono; Hadi Susanto (Universitas Djuanda, 2023)
Effective maintenance of a university campus building is crucial to ensure the safety and well-being of its academic community. However, maintaining the building and its various equipment and assets can take time and effort. This study aims to optimize building maintenance by implementing Business Process Reengineering (BPR) and using an Excel-based application system to detect points of damage. The study analyzes the maintenance process's cost, duration, and damage reports using dashboard features such as Gantt chart diagrams. By comparing the Excel-based application system with the conventional system, we found that the former is more effective and efficient. The results show that the application system saves 12 hours of recapitulation time per week, increases labor productivity by 32.2%, and speeds up damage reparation by 5%.